Closed form expressions for the volume of the GPS ambiguity search space. - Teunissen, Peter (1997)
In this contribution we present closed form expressions for the volumes of the GPS ambiguity search spaces. This is done for the geometry-free model. We also discriminate between single-frequency data and dual-frequency data, and between phase-only cases and phase and code cases. Our results provide an intrinsic precision description of the least squares ambiguities and explicit show the various factors that influence it.